Knowledge-oriented business process management as a catalyst to the existence of network organizations - Olga Sobolewska (Journal of Entrepreneurship, Management and Innovation)
Nowadays, more and more often, we are dealing with the emergence of network organizations. These are organizations set up to accomplish specific tasks and are created by unrelated organizations. Choosing such a partner cannot be and is not accidental. It is a process in which knowledge about a possible partner and its resources as well as opportunities are used. The author puts forward the thesis that the organization’s orientation both on business processes and knowledge management is a strong determinant for undertaking network cooperation. In order to verify such a formulated question, a questionnaire was carried out. Questions about factors influencing the decision about undertaking cooperation in the network structure were directed to a non-random group. The organizations that participated in the study have experience in running projects within the network structure. The study is of a contributing nature, but it can be a starting point for further considerations and for an attempt to build a model of a general nature.